Mentalitas Kepiting Siswa SMA: Cermin dari Harga Diri dan Persepsi Iklim Kelas? - Istifa Rahmasanty, Zakkiyah; Mardhiyah, Zahrina (INSAN Jurnal Psikologi dan Kesehatan Mental, 2025)
This study aims to examine the correlations between perceived classroom climate and self-esteem with the tendency toward the crab mentality among high school students. Crab mentality refers to a behavioral tendency to undermine others’ success due feelings of insecurity.  This study used a quantitative approach on 190 high school students selected through proportionate stratified random sampling. The instruments used include a self-esteem scale, a classroom climate scale, and a crab syndrome scale with reliability > 0.80. Data analysis was conducted with multiple regression. The results showed a significant negative relationship between perceived classroom climate and self-esteem with crab mentality. In addition, differences in the tendency of crab mentality were found based on grade level. These findings emphasize the importance of developing healthy self-esteem and creating a supportive classroom environment to prevent the emergence of the “if I can't do it, neither can them” mindset.